'Obras en la Colección del Museo Würth', La Rioja : Christo & Jeanne-Claude (2009)
Presentación de la obra de los artistas estadounidenses en España.
Keywords: CHRISTO AND JEANNE-CLAUDE; CHRISTO, VLADIMIROV JAVACHEFF; DENAT DE GUILLEBON, JEANNE-CLAUDE; ARTE; EXPOSICIONES; ESPAÑA; LA RIOJA